The Effect of Learning Attitudes and Study Habits on Students' Biology Learning Outcomes in Public Senior High Schools - Nabila Nur Syahirah; Muhiddin Palennari; Muhammad Arsyad; Firdaus Daud; Halimah Husain (Postgraduate, University of Mataram, 2026)
This study aims to analyze the effect of learning attitudes and study habits on students’ biology learning outcomes in Public Senior High Schools across Kendari City. This research employed a quantitative approach with an ex post facto design involving 185 eleventh-grade students selected through proportional random sampling. Data were collected using Likert-scale questionnaires and documentation, and analyzed using descriptive and inferential statistics. The results showed that learning attitudes, study habits, and biology learning outcomes were generally in the moderate category, with mean scores of 91.86, 89.29, and 70.28, respectively. The results of the inferential analysis showed that learning attitudes had a positive and significant effect on biology learning outcomes with a contribution of (20.9%); study habits had a positive and significant effect on biology learning outcomes with a contribution of (17.9%); and learning attitudes and study habits simultaneously had a significant effect on students’ biology learning outcomes with a contribution of (21.1%), with learning attitudes as the more dominant variable.